Effects of sodium fluoride on neural tube development in chick embryos - AKAKIN, DİLEK (My University, 2023)
Objective: Various environmental factors encountered in daily life are associated with the development of neural tube defects. This study aims to investigate the effects of fluoride on neural tube development in chick embryos. Methods: A total of 60 specific pathogen-free, fertile, zero-day Leghorn-type eggs were used in the study. Group 1 was the control group, in which only saline was administered. Group 2 was the low-dose group, in which 0.003 mg of fluoride was administered, and Group 3 was the high-dose group, in which 0.006 mg of fluoride was administered. After 72 h of incubation, the embryonic disc was evaluated microscopically. Results: In the control group, the surface ectoderm of all sections was intact, the neural tube was closed, and the neuroepithelium, the basement membrane surrounding the neuroepithelium, the somites, and the notochord displayed standard structure. Neural tube defects were observed in 3 of the chick embryos, that was given low-dose fluoride. In Group 3, which was administered high doses of fluoride, neural tube defects were observed in 4 embryos. It was observed that the development of neural tube defects was no statistically significantly higher in low and high-dose fluoride group compared to the control group. Conclusion: Low and high-dose fluoride exposure was associated with developing neural tube defects, but there was no statisticaly significance.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; CLINICAL NEUROLOGY; Cerrahi; Nöroloji (klinik); Surgery; Neurology (clinical); Early chick embryo; Fluoride; Neural tube defect; Sodium fluori